Shades of the American Dream - Dorothy A. Brown (Washington University Law Review, 2009)
Federal tax policies such as the mortgage interest deduction do not generally encourage anyone to become a homeowner, yet they do increase the cost of housing. Low-income homeowners regardless of race are least likely to be able to take advantage of the mortgage interest deduction. They pay for a benefit that they cannot receive. Middle- and upper-income black homeowners are less likely than middle- and upper-income white homeowners to benefit from federal tax laws supporting homeownership in different ways. The appreciation of most middle- and upper-income black homes is significantly less than the appreciation of middle- and upper income white homes. As a result, those black homeowners will not benefit as much as white homeowners from the tax provisions that exclude from income gain on the sale of their homes. This Article suggests three solutions which, if enacted, would cause the tax benefits to be more equitably distributed and no longer concentrated in the hands of higher income, white taxpayers.
Keywords: Taxation; Tax credits; Low-income housing; Equitable distribution of marital property; Race discrimination